Periodontal regeneration with autologous periodontal ligament-derived cell sheets – A safety and efficacy study in ten patients - Iwata, Takanori; Yamato, Masayuki; Washio, Kaoru; Yoshida, Toshiyuki; Tsumanuma, Yuka; Yamada, Azusa; Onizuka, Satoru; Izumi, Yuichi; Ando, Tomohiro; Okano, Teruo; Ishikawa, Isao (Regenerative therapy, 2018)
Periodontitis results in the destruction of tooth-supporting periodontal tissues and does not have the ability to heal spontaneously. Various approaches have been introduced to regenerate periodontal tissues; however, these approaches have limited efficacy for treating severe defects. Cytotherapies combine stem cell biology and tissue engineering to form a promising approach for overcoming these limitations. In this study, we isolated periodontal ligament (PDL)-derived cells from patients and created cell sheets with “Cell Sheet Engineering Technology”, using temperature responsive culture dishes, in which all the cultured cells can be harvested as an intact transplantable cell sheet by reducing the temperature of the culture dish. Subsequently, the safety and efficacy of autologous PDL-derived cell sheets were evaluated in a clinical setting. A single-arm and single-institute clinical study was performed to verify the safety and efficacy of autologous PDL-derived cell sheets in patients with periodontitis. Wisdom teeth were extracted from patients diagnosed with chronic periodontitis, ranging in age from 33 to 63 years (mean [±SD], 46 ± 12), and periodontal tissues were scraped for cell sources. Three-layered PDL-derived cell sheets were constructed using temperature-responsive culture dishes and transplanted in an autologous fashion following standard flap surgeries. Bony defects were filled with beta-tricalcium phosphate granules. Clinical variables were evaluated at baseline, 3 months, and 6 months. Cone-beam computed tomography was performed at baseline and 6 months. Additionally, mid-long-term follow-up has been performed with patients’ agreements. Our method was found to be safe and no severe adverse events were identified. All the findings, including reduction of periodontal probing depth (mean ± SD, 3.2 ± 1.9 mm), clinical attachment gain (2.5 ± 2.6 mm), and increase of radiographic bone height (2.3 ± 1.8 mm), were improved in all 10 cases at 6 months after the transplantation. These therapeutic effects were sustained during a mean follow-up period of 55 ± 19 months, and there were no serious adverse events. The results of this study validate the safety and efficacy of autologous PDL-derived cell sheets in severe periodontal defects, and the stability of this efficacy during mid-long-term follow up. This cytotherapeutic approach, based on cell sheet engineering, offers an innovative strategy to treat the recognized unmet need of treating severe periodontal defects.